Kepemimpinan Kepala Sekolah dalam Manajemen Kinerja Guru dan Peningkatan Mutu Pembelajaran di SMP Swasta Dwiwarna - Aswaruddin A; Amar Khairi Ahmad; Anggun Sari Fadilla; Dwi Hartina; Rosa Marshanda (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The problem of the study was the leadership of the Principal in the management of teacher performance and the improvement of the quality of learning at Dwiwarna Private Junior High School in Medan City. The established research method is descriptive-analytical research using a qualitative approach. The location chosen as the research site is at Jl. Arca Building No. 52. While the subjects sampled for the study were the Principal and some teachers. The leadership of the Principal was judged to be very effective in the management of improving the performance of teachers at Dwiwarna Private Junior High School. The leadership strategy of the Principal in improving the quality of learning in Dwiwarna Private Junior High School in general can be grouped through the following steps: (1) The Principal always fosters the commitment of all teachers to uphold the spirit and values that have been established together; (2) The Principal along with all the relevant teachers evaluates the extent to which the overall components of the school system can go for the advancement of the school; and (3) Develop the school culture as an implementation and institutionalization that leads to working habits within and outside of school.